Reliability of a semi-tethered front crawl sprint performance test in adolescent swimmers - Szczepan, Stefan; Wróblewska, Zofia; Klich, Sebastian; Michalik, Kamil; Gonjo, Tomohiro; Olstad, Bjørn Harald; Rejman, Marek (Frontiers in Physiology, 2023)
This study aimed to evaluate the test-retest reliability of a sprint performance test with semi-tethered front crawl swimming to indirectly assess the current potential to perform at maximal anaerobic effort in adolescent swimmers. Eight adolescent swimmers participated in this study (gender: females (n=4) aged 13.0 ± 0.8 years, body height 1.6 ± 0.0 m, body mass 50.1 ± 4.5 kg; and males (n=4) aged 13.3 ± Semi-tethered swimming test in adolescent swimmers 2 1.3 years, body height 1.7 ± 0.1 m, body mass 59.0 ± 8.2 kg. The testing protocol consisted of two trials of 25 m semi-tethered front crawl swimming with maximal effort and with 1 kg resisted isotonic load. Velocity data were recorded automatically by the 1080 Sprint device for 15 meters (between 3 meters and 18 meters). The Fast Fourier Transform algorithm filtered raw instantaneous swimming velocity data in distance (time) function. A third-degree polynomial was used to extract the individual velocity profile, from which the following variables were chosen for test-retest reliability and the assessment of sprint performance: ttrial15, vmax, vmin, tvto max, tvat max, Dto vmax, Dat vmax, FI. Parameters such as vmax, vmin, and ttrial15 were estimated from swimming velocity profiles and considered as reliable.The CV showed low variance <5%; while ICC2,1 demonstrated respectively good (ICC2,1: 0.88), very good (ICC2,1: 0.95), and excellent (ICC2,1: 0.98) rate of relative reliability; and the Bland-Altman index revealed an acceptable agreement (LoA ≤5%) between two measurements. The sprint performance test based on semi-tethered front crawl swimming confirmed that ttrial15, vmax, and vmin were reliable variables to indirectly indicate a potential to perform the maximal anaerobic effort among adolescent swimmers. The evaluation of the swimming velocity profiles allows coaches to monitor the adaptive changes of performance during the training process.